‘Under a Curse’: a Fresh Reading of Galatians 3.10–14 - Stanley, Christopher D. (New Testament studies, 1990)
Though Martin Luther was doubtless not the first student of the NT to notice the apparent discrepancy between Paul's general affirmation in Galatians 3. 10a and the citation he introduces to support it in 3.10b, his statement of the problem has scarcely been improved upon in the centuries that have followed. As it stands, the Pauline text does present something of a conundrum. Whereas Paul's own statement appears to pronounce a ‘curse’ upon anyone who would attempt to live by the Jewish Torah, the biblical text to which he appeals clearly affirms the opposite: its ‘curse’ falls not on those who do the Law, but on those who fail to do it. What is Paul trying to say? Does he simply misunderstand his citation at this point? Or is there an underlying link between text and ‘interpretation’ that is not evident at first sight?